Caracterización físico -químicas y sensorial de quince clones de cacao (theobroma cacao l.) tipo nacional en almendras fermentadas y secas para obtención de pasta de cacao - Párraga Moran, Dayse Evelina (2013)
This research was conducted in the laboratory of food science of the faculty of animal science. State technical university Quevedo, will be located; located in the km 7 of the track Quevedo splice. Province of los Rios, Ecuador. Its geographical location is 1° 6 2.30" of south latitude and 79° 29' 30" west longitude, at an altitude of 124 meters above sea level. The purpose of this work was to carry out the "physic-chemical characterization and sensory of fifteen cacao clones (theobroma cacao l). National kind in almonds and fermented dry to obtain cocoa paste during the months of February to June of 2013. The fifteen treatments consisting the clones were distributed in the field of design completely random with 3 replications. The variables measured were, temperature (T°), pH, seed index (IS), Index of cob (IM), Dry weight (PS), Number of almonds (NA), Diameter cob (DM), Weight test (PT), Weight cotyledon (PC), Number of kernels per ear (NAM), Weight of 100 almonds (P100A), Percentage of test (%T), Determination of the pH in the test and cotyledon (DPHT), Percentage of theobromine (%TEO) and caffeine (C), The process of pasta (liqueur) Cocoa, was used for mean comparison Tukey test 5% the probability. In terms of the results obtained, the largest index of cob was presented in the T6 (DIRCYT-C129) With 34.36gr. Although statistically equal to the rest. Simultaneously the largest seed index was recorded in the T2 (DIRCYT-c103), with 1,65 g for data on the weight of 100 seeds presented numerical differences with the witness T13 CCN-51 with the highest recorded weight 165,67 grams of sensory assessment this were carried out by the panel of cupping the INIAP-aka. The liquors were qualified with a sensory scale from zero to five points, where zero represents the absence of that particular flavor, and five the maximum intensity of the same. The final five were selected materials of organoleptic profiles balanced. The highest intensity corresponds to the cocoa flavor and less to the sweet taste of the witness shows T14 IMC-67 with 5.33. It is concluded that under these climatic conditions these materials have a good performance and develop good characteristics of precocity. It is also recommended to confirm the organoleptic profiles obtained for the selected material and then continue with circulations tests to evaluate their adaptation, productivity and organoleptic profiles in of three areas of interest.